Empagliflozin Reduces Renal Hyperfiltration in Response to Uninephrectomy, but Is Not Nephroprotective in UNx/DOCA/Salt Mouse Models - Tauber, Philipp; Sinha, Frederick; Berger, Raffaela S.; Gronwald, Wolfram; Dettmer, Katja; Kuhn, Michaela; Trum, Maximilian; Maier, Lars S.; Wagner, Stefan; Schweda, Frank (Frontiers in Pharmacology, 2021)
Large-scale clinical outcome studies demonstrated the efficacy of SGLT2 inhibitors in patients with type II diabetes. Besides their therapeutic efficacy in diabetes, significant renoprotection was observed in non-diabetic patients with chronic kidney disease (CKD), suggesting the existence of glucose-independent beneficial effects of SGLT2 inhibitors. However, the relevant mechanisms by which SGLT2 inhibition delays the progression of renal injury are still largely unknown and speculative. Previous studies showed that SGLT2 inhibitors reduce diabetic hyperfiltration, which is likely a key element in renoprotection. In line with this hypothesis, this study aimed to investigate the nephroprotective effects of the SGLT2 inhibitor empagliflozin (EMPA) in different mouse models with non-diabetic hyperfiltration and progressing CKD to identify the underlying diabetes-independent cellular mechanisms. Non-diabetic hyperfiltration was induced by unilateral nephrectomy (UNx). Since UNx alone does not result in renal damage, renal disease models with varying degrees of glomerular damage and albuminuria were generated by combining UNx with high NaCl diets + deoxycorticosterone acetate (DOCA) in different mouse strains with and without genetic predisposition for glomerular injury. Renal parameters (GFR, albuminuria, urine volume) were monitored for 4-6 weeks. Application of EMPA via the drinking water resulted in sufficient EMPA plasma concentration and caused glucosuria, diuresis and in some models renal hypertrophy. EMPA had no effect on GFR in untreated wildtype animals, but significantly reduced hyperfiltration after UNx by 36 %. In contrast, EMPA did not reduce UNx induced hyperfiltration in any of our kidney disease models, regardless of their degree of glomerular damage caused by DOCA/salt treatment. Consistent with the lack of reduction in glomerular hyperfiltration, EMPA-treated animals developed albuminuria and renal fibrosis to a similar extent as H2O control animals. Taken together, the data clearly indicate that blockade of SGLT2 has the potential to reduce non-diabetic hyperfiltration in otherwise untreated mice. However, no effects on hyperfiltration or progression of renal injury were observed in hypervolemic kidney disease models, suggesting that high salt intake and extracellular volume might attenuate the protective effects of SGLT2 blockers.